Political and Social History c. 1780–1832 - Sedlmayr, Gerold (De Gruyter, 2017)
This article presents a concise overview of important political and social developments from c. 1780 to 1832. In order to offer some basic coordinates concerning the political framework, it begins by asking whether the period in question marks the beginning of a two-party system and also outlines the position of the monarch. In a next step, the effects of the French Revolution on Britain are discussed, particularly with a view to the pamphlet war it engendered and the repressive measures the government took to stifle revolutionary tendencies at home. A consideration of Britain’s long and debilitating involvement in the Revolutionary and Napoleonic Wars follows. This is then complemented by a subchapter on pro-independence and revolutionary movements in Ireland, which ultimately culminated in the constitutional union with Britain in 1801. The next section focuses on the Empire at large, predominantly its ‘Swing to the East’ after the loss of the North-American colonies. Subsequently, the impact of the Industrial Revolution is briefly discussed, along with a consideration of class structures. The last subchapter concentrates on the issue of parliamentary reform, which ultimately was accomplished through the Reform Act of 1832.
CRIS-Team Scopus Importer:2024-10-02
Keywords: 1780–1832; British Empire; British history; Impact of French Revolution; Ireland; Napoleonic wars; political reform